The natural and the social that we all are, the human beings: Reflections about knowledge, subjectivity, and food - Donizete PRADO, Shirley; Baiocchi de CARVALHO, Kenia Mara; AMPARO-SANTOS, Ligia (Revista de Nutrição, 2023)
This Thematic Section brings themes situated in the scope of discussions relating to the epistemological bases that guide the field of Food and Nutrition, more specifically, studies derived from the presentations composing the 5th Seminar of Graduate Methods in Food and Nutrition organized by the National Forum of Coordinators of Graduate Programs in Food and Nutrition. This event took place during the 12th National Congress of the Brazilian Society of Food and Nutrition in the city of Foz do Iguaçu, Paraná, in August 2013.